『여씨춘추』의 군도로서 ‘무위’ 연구 - 김태용; Kim Taeyong (중국학보, 2025)
이 논문은 『여씨춘추』에서 군도로서 무위가 갖는 내용과 의미를 고찰한다. 『여씨춘추』에서 ‘무위’는 군주만이 따르고 실천하는 도리이다. 군도로서 ‘무위’는 군주가 자연 본성에 순응하여 평안함과 고요함을 유지할 뿐, 몸소 나서 일하지 않고 감독하여 살피는 것을 의미한다. 군주는 몸소 나서 일하지 않기에 ‘유위’를 신도로 하는 신하를 효율적으로 이용해야만 ‘무위’의 정치를 실현할 수 있다. ‘무위’를 따르는 군주에게는 공리를 추구하고 국력과 국론을 통일시키며 백성을 아끼고 다른 사람의 장점을 이용하는 역량이 요구된다. ‘유위’를 실천하는 신하에게는 직무 수행 역량, 좋은 인품 이외에 자신의 능력을 알고 도의와 정당함을 따르며 바른 말로 간언하고 미래 세대와 공익을 생각하는 자세가 요구된다. 군주와 신하에게 공통으로 자신들의 이익이 아닌 인민의 이익을 위해 일하려는 마음가 짐과 자세가 요구된다. 그리고 군주는 신하를 부릴 수 있는 상벌의 권세를 강화하고 유지할 줄 알아야 한다. 『여씨춘추』에서 군도로서 ‘무위’의 실행은 군신 상하의 직분을 정하는 것부터 시작된다. 다음으로 군주는 시세 특히 민심에 순응하여 국정 운영 방향과 과제를 정하고 직책과 그에 해당하는 직무가 상호 부합하도록 조정한다. 마지막으로 상벌의 권세를 쥔 군주는 신하의 역량에 따라 국무를 나누어 맡긴 후, 직책에 따라 직무 수행 결과를 평가하여 신하에게 책임을 묻는다. 『여씨춘추』에서 군도로서 ‘무위’란 인민의 이익을 위해 ‘무위’를 실천하는 군주와 ‘유위’를 실천하는 신하가 서로 협력하여 민심에 순응해 국정을 운영하는 통치술이다. 그리고 『여씨춘추』에서 군주의 ‘물신’과 ‘독청’그리고 신하의 ‘유위’를 포괄하는 군도로서 ‘무위’는 소극적·수동적인 측면과 적극적·능동적인 측면이 어우러진 통치술이다. This paper examines the content and meaning of ‘Wuwei’ as the political principles of a monarch in 『Lushi Chunqiu』. In 『Lushi Chunqiu』, ‘Wuwei’ is the political principles that only the monarch follows and practices. ‘Wuwei’ as the political principles of a monarch means that the monarch conforms to his nature and keeps inner peace, and does not personally take the initiative to do anything, but supervises and observes. Since the monarch does not personally take action, he must effectively utilize his subjects who consider ‘Youwei’ as the political principles of a subject to realize the politics of ‘Wuwei’. A monarch who follows ‘Wuwei’ is required to have the competences of pursuing public interest, unifying national power and national opinion, caring for the people, and utilizing the strengths of others. A subject who practices ‘Youwei’ is required to have the attitudes of knowing his own abilities, following morality and justice, advising with the right words, considering the future generations and the public interest, in addition to competence to perform job duties, good character. Both the monarch and his subjects are required to have the common attitude and mindset of working for the benefit of the people, not for their own benefit. And the monarch must know how to strengthen and maintain the power to reward and punish his subjects. In 『Lushi Chunqiu』, the practice of ‘Wuwei’ as the political principles of a monarch begins with determining the positions of the monarch and his subjects. Next, the monarch determines the direction of state affairs and tasks in accordance with the state of the times, especially the public sentiment, and adjusts the positions and their corresponding duties so that they are mutually compatible. Finally, the monarch, who holds the power of reward and punishment, divides state affairs according to the abilities of his subjects, and then evaluates their job performance results according to their positions and holds them accountable. ‘Wuwei’ as the political principles of a monarch in 『Lushi Chunqiu』 refers to the art of governance in which a monarch who practices ‘Wuwei’ and a subject who practices ‘Youwei’ cooperate with each other to run the country in accordance with the will of the people for the benefit of the people. And In 『Lushi Chunqiu』 ‘Wuwei’ as the political principles of a monarch, which encompasses the monarch’s ‘Don’t do the work yourself’ and ‘Supervising and watching’ and the subject’s ‘Youwei’, is a method of governing that combines both passive and active aspects.